Meat Production and Supply Chain Under COVID-19 Scenario: Current Trends and Future Prospects - Ijaz, Muawuz; Yar, Muhammad Kashif; Badar, Iftikhar Hussain; Ali, Sher; Islam, Md. Shafiqul; Jaspal, Muhammad Hayat; Hayat, Zafar; Sardar, Aneeqa; Ullah, Sana; Guevara-Ruiz, Denise (Frontiers in Veterinary Science, 2021)
The COVID-19 pandemic impacted meat production, supply chain, and meat prices that caused a severe socio-economic crisis worldwide. Initially, meat and meat products' prices increased due to less production and increased demand because of panic buying. Whereas, later on, both meat production and demand were significantly decreased due to lockdown restrictions and lower purchasing power of the consumers that results in a decrease in meat prices. In early April 2020, meat packing facilities started to shut down due to the rapid spread of the COVID-19 virus among workers. Furthermore, meat producers and processors faced difficulty in harvesting and shipment of the products due to lockdown situations, decrease in labor force, restrictions in movement of animals within and across the country and change in legislation of local and international export market. These conditions adversely impacted the meat industry due to decrease in meat production, processing and distribution facilities. It is suggested that the integration among all the meat industry stakeholders is quite essential for the sustainability of the industry's supply chain to cope with such devastating conditions the future may hold. This review aimed to discuss different aspects of the meat industry and supply chain during the COVID-19 pandemic and proposed some future directions.